(untitled) (Research, Society and Development, 2022)
This article reports a case of tracheal pythiosis in a dog with a clinical symptom of cough followed by retching with a suspected foreign body. Radiographic imaging showed a mass with soft tissue density in the tracheal lumen. The patient underwent an emergency tracheostomy due to respiratory failure caused by the obstruction, during which we found a reddish granulomatous, well-delimited macroscopic structure in the cervical segment of the trachea. The histopathological microscopic examination of the fragment revealed a granulomatous transmural tracheitis associated with hyphae compatible with Pythium insidiosum. The hyphae were strongly immunostained with anti-Pythium insidiosum polyclonal antibody, confirming the diagnosis of pythiosis based on epidemiology, clinical, and histopathological findings. However, 12 hours after the surgery, the animal died due to cardiopulmonary arrest.